DEVELOPMENT AND EVALUATION OF CYCLODEXTRIN NANOSPONGES-BASED TOPICAL FORMULATION OF TAZAROTENE - PRATAP, RAVINDRA; LANKALAPALLI, SRINIVAS (International Journal of Applied Pharmaceutics, 2024)
Objective: Tazarotene is used as a topical retinoid for the treatment of acne, psoriasis and sun-damaged skin. But its topical formulation has many side effects, including itching, burning, dryness, redness, stinging, rash blistering, skin discoloration, peeling at the site of application and low bioavailability. The present study focuses on the reduction of side effects and enhancement of solubility and topical bioavailability of tazarotene by using cyclodextrin-based nanosponges. Methods: Nanosponge of tazarotene were prepared by lyophilization method. The physiochemical characterization of plain nanosponges and drug-loaded nanosponges were performed using Fourier Transform Infrared Spectroscopy (FTIR), Differential Scanning Calorimetry (DSC), and X-ray Diffractometer (XRD) studies. The drug-loaded nanosponges were incorporated into a carpool-based gel formulation. The prepared formulation was evaluated for viscosity, dissolution and stability. FTIR, DSC and XRD studies confirmed the formation of inclusion complex of tazarotene with nanosponges. Results: The particle size of the drug-loaded nanosponges was found to be in the range of 156.72 to 163.48 nm. Transmission Electron Microscopy (TEM) images revealed the regular spherical shape of both the nanosponges that are unaffected even after drug encapsulation. The pH of the gel formulations was found to be in the range of 5.86 to 6.46. The gel formulation resulted in the diffusion of drug in controlled manner for up to 24 h. The in vitro dissolution studies revealed that nanosponges-based topical formulation had better results than the marketed product. Conclusion: Thus, the study showed that nanosponge-based gel formulation can be a possible alternative to conventional formulations of tazarotene with enhanced bioavailability and skin retention characteristics for topical application.